Identity and internationalization in Catholic universities : exploring institutional pathways in context - Wit, Hans de, 1950-; Bernasconi, Andrés; Car, Visnja (Visnja Schampers-Car); Hunter, Fiona, 1957-; James, Michael, Ph. D.; Veliz, Daniela (Global perspectives on higher education, 2018)
"Identity and Internationalization in Catholic Universities explores the relationship between Catholic identity, mission, and internationalization in Catholic universities of different types and located in different contexts. Internationalization is a key concern for universities working to achieve their goals in different regions of the world but without neglecting their identity. There are many universities that consider themselves related to the Roman Catholic faith and many other universities with Christian affiliations. It is well known that Catholic universities have unique missions, such as the formation of individuals inspired by a religious conviction to serve society and the church. That is why it is imperative to have empirical knowledge to help develop practical and effective policies on central themes such as internationalization, a fundamental part of many universities' developmental strategies, while paying special attention to each university's specific context. This book includes sixteen case studies from Latin America, the United States, the Asia Pacific, and Europe, and also includes chapters on regional perspectives on Catholic higher education as well as more specifically Jesuit higher education, the global network of La Salle universities, and internationalization in the United States, Latin America, the Asia Pacific region, and Europe"--